2013
DOI: 10.4155/fmc.13.151
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Inhibitors of Human Ldh5

Abstract: The latest findings on the role played by human LDH5 (hLDH5) in the promotion of glycolysis in invasive tumor cells indicates that this enzyme subtype is a promising therapeutic target for invasive cancer. Compounds able to selectively inhibit hLDH5 hold promise for the cure of neoplastic diseases. hLDH5 has so far been a rather unexplored target, since its importance in the promotion of cancer progression has been neglected for decades. This enzyme should also be considered as a challenging target due the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 94 publications
1
70
0
1
Order By: Relevance
“…6 Therefore, several recent research efforts have been dedicated to the development of new LDH-A inhibitors with therapeutic potential as anticancer drugs, although problems related to poor cellular activities of these inhibitors have been often reported. 7,8 …”
Section: Introductionmentioning
confidence: 99%
“…6 Therefore, several recent research efforts have been dedicated to the development of new LDH-A inhibitors with therapeutic potential as anticancer drugs, although problems related to poor cellular activities of these inhibitors have been often reported. 7,8 …”
Section: Introductionmentioning
confidence: 99%
“…5 LDH family includes three isoenzymes, namely, lactate dehydrogenase A (LDHA), lactate dehydrogenase B (LDHB) and lactate dehydrogenase C (LDHC). LDHA is abundant in skeletal muscle, 6 and LDHB is predominantly expressed in the brain and heart, 7 but LDHC is strictly limited to the testis, which is essential for maintaining glycolysis and producing adenosine triphosphate (ATP) in spermatogenesis. [8][9][10][11][12] In particular, recent researches have showed LDHC is expressed in a broad spectrum of tumours, with frequent appearance in lung cancer, melanoma and breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Measured by immunohistochemistry, our previous study demonstrated LDH‐5 expression, which is the most efficient isoenzyme catalyzing the conversion of pyruvate to lactate as an independent prognostic factor for reduced tumor‐specific survival in OSCC . Therefore, focusing on the LDH‐5 isoform (M subunit) is of potential therapeutic interest by targeted therapies ( e.g., small compounds) for oncologists .…”
Section: Discussionmentioning
confidence: 99%